Heavy metal(loid)s in fruit-growing soil of tropical Hainan Island in China: Pollution, ecological-health risks, spatial assessment, and source analyses - Wu, Xiaofang; Zhou, Cailin; Xie, Yi; Wang, Xiaogang; Deng, Aini (International Journal of Agricultural and Biological Engineering, 2023)
Hainan Island is the most important tropical fruit production area in China. In this study, 372 soil samples and corresponding fruit and irrigation water samples were collected from Hainan orchards and analysed to determine the concentrations of six heavy metal(loid)s: Cd, Hg, As, Pb, Cr, and Cu. The pollution status, potential risks, possible sources, and spatial distribution patterns of soil heavy metal(loid)s were comprehensively investigated. The fruit and irrigation water samples had negligible amounts of heavy metal(loid)s, and the potential human health risk for fruit consumers was at a safe level. The heavy metal(loid) concentrations in most soil samples were lower than the national risk screening values. However, significant local accumulation of heavy metal(loid)s, especially Cd, Cr, and Cu, relative to their background values was observed. Moreover, the combined effects of the heavy metal(loid)s only led to a mild pollution level and low ecological risk throughout the study area. Noncarcinogenic risks were not observed among the local residents, and carcinogenic risks were within an acceptable range. The acidic soil in the study area increased the risk of soil Cd pollution, and organic matter affected the distribution of the tested metal(loid)s in the soil. Uncommon geogenic sources with high background values were the sources of Cr and Cu, anthropogenic activities primarily led to Cd, Pb, and As contamination, and a combination of anthropogenic and natural sources was responsible for Hg emissions. The research suggested that appropriate strategies must be implemented to track and reduce soil heavy metal contaminants in the northern and western region of the Hainan orchard area. The results can provide valuable information for policies on pollution prevention and management, the environment, and human health protection in the study region. Keywords: heavy metal(loid)s, Hainan Island, orchard, pollution assessment, ecological-health risk assessments, spatial distribution, source analysis DOI: 10.25165/j.ijabe.20231604.8011 Citation: Wu X F, Zhou C L, Xie Y, Wang X G, Deng A N. Heavy metal(loid)s in fruit-growing soils of tropical Hainan Island in China: Pollution, ecological-health risks, spatial assessment, and source analyses. Int J Agric & Biol Eng, 2023; 16(4): 231–244.